Industry 4.0: Challenges, Opportunities, and Strategic Solutions for Bangladesh - Bhuiyan, Abul Bashar; Ali, Md. Jafor; Zulkifli, Norhayah; Kumarasamy, Mokana Muthu (International Journal of Business and Management Future, 2020)
In the recent decade, the term Industry 4.0 or Fourth Industrial Revolution is a common buzzword represents the adoption of disruptive digital technologies (Internet of things, Big Data, 3D printing, Cloud computing, Autonomous robots, Virtual reality, Augmented reality, Self-driving car, Cyber-physical system, Artificial intelligence, Smart sensors, Nanotechnology, Drones, and Biotechnology, etc.) in the production process which is transforming the manufacturing units into smart factories and experiencing a great change in the global value chain. Moreover, these revolutionary digital technologies have a profound impact on the economy, growth, globalization, governments, international trade, global supply chain, and human capital transformation, etc. The present review study aims to explore the impact, challenges, and opportunities of the fourth industrial revolution based on empirical findings specially and extensively in the context of Bangladesh. The study finds regardless of having enormous potentiality, the application of the fourth industrial revolution is far lagging for some challenges i.e. lack awareness, insufficient capital, lack of infrastructure, lack of skilled human capital, and some socio-economic challenges. This review paper will also develop conceptual links with the relevant aspect of strategic planning and application of key industry 4.0 technologies and help to formulate future policy guidelines regarding opportunities, application, and strategic decision making for the fourth industrial revolution in Bangladesh.